Characteristic behavior of soil using bacterial biogrouting with LISA FEA V.8. - Aco Wahyudi Efendi (International Journal of Advanced Science and Computer Applications, 2024)
The increasingly widespread use of micro-bacteria in research to improve soil characteris-tics in the world of construction and also provide a significant increase in soil carrying ca-pacity so that this kind of research makes a very good contribution where the material and mixing object are natural materials, namely in the form of bacteria. This study used the finite element method with the help of LISA V.8 FEA (Li-cense), a finite element method software package, to obtain the stress arising from existing soil ma-terial with soil material that has been mixed with mycobac-teria or the biogrouting method. According from the results of the analysis using numerical analysis using the finite el-ement method LISA V.8 FEA program, it can be seen that there is a reduc-tion in the oc-currence of settlement after adding the two bacteria which have been aged for 30 days with a reduction in soil settlement of 2.9-2.27 mm de-spite an increase in stress. ranging from 58.3 to 69.4 kN/m2.